2015
DOI: 10.1080/01652176.2015.1068963
|View full text |Cite
|
Sign up to set email alerts
|

Phylo-typing of clinicalEscherichia coliisolates originating from bovine mastitis and canine pyometra and urinary tract infection by means of quadruplex PCR

Abstract: (2015) Phylo-typing of clinical Escherichiacoli isolates originating from bovine mastitis and canine pyometra and urinary tract infection by means of quadruplex PCR, Veterinary Quarterly, 35:4, 194-199, DOI: 10.1080/01652176.2015 Background: Escherichia coli is one of the major causative agents of bovine mastitis worldwide, and is typically associated with acute, clinical mastitis. Besides this, E. coli strains which belong to the extra-intestinal pathogenic group are also the major cause of urinary tract in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
2
19
1
Order By: Relevance
“…The new Clermont method revealed that the isolates assigned as phylo-group B2 9/12 (75.0%), B1 2/5 (40.0%) and A 2/7 (28.6%) by using the old Clermont method could not be phylotyped, consequently they were grouped as unknown or non-typeable strains of MDR E. coli. This kind of alteration of the phylogenetic groups of E .coli from old Clermont to the new Clermont method was also reported by Müştak et al (2015), although to different sets of phylogenetic groups. In 2013 Clermont and his colleagues were unable to detect these phylogenetic groups (---+, --+ +, + -+ + and + + + +) using the new Clermont method, despite the enormous work they did to screen over 1000 E. coli strains (Clermont et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…The new Clermont method revealed that the isolates assigned as phylo-group B2 9/12 (75.0%), B1 2/5 (40.0%) and A 2/7 (28.6%) by using the old Clermont method could not be phylotyped, consequently they were grouped as unknown or non-typeable strains of MDR E. coli. This kind of alteration of the phylogenetic groups of E .coli from old Clermont to the new Clermont method was also reported by Müştak et al (2015), although to different sets of phylogenetic groups. In 2013 Clermont and his colleagues were unable to detect these phylogenetic groups (---+, --+ +, + -+ + and + + + +) using the new Clermont method, despite the enormous work they did to screen over 1000 E. coli strains (Clermont et al, 2013).…”
Section: Discussionsupporting
confidence: 70%
“…We focused our present analysis on phylogroup A for three principal reasons. Firstly, since phylogroup A are most often identified as amongst the most abundant phylogroup recovered from cases of bovine mastitis 10 11 12 13 14 , we wanted our study to have particular relevance to this predominant and problematic group. Secondly, since we speculated that selection plays a key role in determining which strains can or cannot elicit mastitis, we used phylogroup A as a discrete monophyletic group where pre-existing evidence pointed to the possibility that this group as a whole becomes enriched in mastitis vis-a-vis the external environment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although E. coli from phylogroups A and B1 are generally considered to be less pathogenic and more likely to be commensals than isolates from other phylogroups 3 7 , these phylogroups do include significant pathogens 8 9 . Indeed, several studies have shown that the vast majority of E. coli isolates from cases of bovine mastitis (termed mammary pathogenic E. coli , or MPEC) originate from within these two phylogroups 10 11 12 13 14 .…”
mentioning
confidence: 99%
“…Phylogenetic analysis is a key to examine E. coli diversity and understand their characteristics in order to establish control programs and settle alterative therapeutic options (40). Our results revealed that, B2 and D groups were the predominant phylogroups in clinical isolates, whereas, A and B1 groups were the most populous among environmental ones ( Figure 1E).…”
Section: Discussionmentioning
confidence: 86%